The Effect of Guest Metal Ions on the Reduction Potentials of Uranium(VI) Complexes: Experimental and Theoretical Investigations. Issue 7 (28th January 2020) - Ghosh, Tanmoy Kumar; Mahapatra, Prithwish; Drew, Michael G. B.; Franconetti, Antonio; Frontera, Antonio; Ghosh, Ashutosh
Abstract: Two mononuclear uranyl complexes, [UO2 L 1 ] (1 ) and [UO2 L 2 ]⋅ 0.5 CH3 CN⋅ 0.25 CH3 OH (2 ), have been synthesized from two multidentate N3 O4 donor ligands, N, N′ ‐bis(5‐methoxysalicylidene)diethylenetriamine (H2 L 1 ) and N, N′ ‐bis(3‐methoxysalicylidene)diethylenetriamine (H2 L 2 ), respectively, and have been structurally characterized. Both complexes 1 and 2 showed a reversible U VI /U V couple at −1.571 and −1.519 V, respectively, in cyclic voltammetry. The reduction potential of the U VI /U V couple shifted towards more positive potential on addition of Li +, Na +, K +, and Ag + metal ions to acetonitrile solutions of complex 2, and the resulting potential was correlated with the Lewis acidity of the metal ions and was also justified by theoretical DFT calculations. No such shift in reduction potential was observed for complex 1 . All four bimetallic products, [UO2 L 2 Li0.5 ](ClO4 )0.5 (3 ), [UO2 L 2 Na(ClO4 )]2 (4 ), [UO2 L 2 Ag(NO3 )(H2 O)] (5 ), and [(UO2 L 2 )2 K(H2 O)2 ]PF6 (6 ), formed on addition of the Li +, Na +, Ag +, and K + metal ions, respectively, to acetonitrile solutions of complex 2, were isolated in the solid state and structurally characterized by single‐crystal X‐ray diffraction. In all the species, the inner N3 O2 donor set of the ligand encompasses the equatorial plane of the uranyl ion and the outer open compartment with O2 O′2 donor sites hosts the second metal ion. Abstract : Complexes and guests : Two mononuclear uranyl complexes were synthesized from two multidentate N3 O4 donor ligands and were structurally characterized. For one complex, a substantial shift in the reduction potential of the U VI /U V couple was observed in the presence of guest metal ions (M + =Li +, Na +, Ag +, K + ). DFT studies showed good agreement with the experimental results.